Resposta de crescimento, matéria seca e fotossíntese do algodoeiro pelo uso de cloreto de mepiquat - Bogiani, Julio Cesar; Rosolem, Ciro Antonio [UNESP] (My University, 2011)
Use of cotton plant growth regulators provides smaller plants, but causes morphology and leaves energy relationships changes. Therefore, this work aimed to study changes in reproductive and vegetative parts of cotton cultivars, as well as the photoassimilates production changes caused by use of mepiquat chloride. The experiment was conducted in greenhouse conditions with six cotton cultivars: 'FMX 966', 'FMX 977', 'DeltaPenta', 'DeltaOpal', 'FMT 501' e 'FMT 701' and four doses of the plant growth regulator "gibberellin synthesis inhibitor" based on mepiquat chloride (0,0 g ha-1 ; 7,5 g ha-1 ; 15,0 g ha-1 and 22,5 g ha-1 of the active ingredient). The experimental design was a 6 x 4 factorial in complete randomized blocks with four replications. Leaf area, dry matter production and drop reproductive structures number decrease by plant growth regulator application, with differences responses among cultivars. Differences in CO2 assimilation rate were not significant among cotton cultivars. All cotton cultivars increased spad index due to increase of dose applied of mepiquat chloride.

O uso de reguladores de crescimento proporciona algodoeiros menores, mas provoca mudanças na morfologia e nas relações de energia das folhas. Dessa forma, o objetivo deste trabalho foi estudar as alterações na parte reprodutiva e vegetativa em cultivares de algodoeiro, bem como alterações na produção de fotoassimilados causadas pelo uso de cloreto de mepiquat. O experimento foi realizado em casa-de-vegetação com seis cultivares: 'FMX 966', 'FMX 977', 'DeltaPenta', 'DeltaOpal', 'FMT 501' e 'FMT 701', e quatro doses do regulador de crescimento "inibidor da síntese de giberelinas" à base de cloreto de mepiquat: 0,0 g ha-1; 7,5 g ha-1; 15,0 g ha-1 e 22,5 g ha-1 de i.a. O delineamento experimental foi em blocos casualizados, com quatro repetições, num esquema fatorial 6 x 4. A área foliar, produção de matéria seca e número de estruturas reprodutivas abortadas decrescem pela aplicação de regulador de crescimento, com diferenças de respostas entre cultivares. As diferenças na taxa de assimilação líquida de CO2 não foram significativas entre as cultivares estudadas. Todas as cultivares apresentam aumento do índice spad pelo uso de cloreto de mepiquat em virtude do aumento da dose aplicada.
Growth, dry matter and photosynthesis response of cotton by using mepiquat chloride
Keywords: Gossypium hirsum L.; Plant growth regulator; Photosynthesis; Gossypium hirsum L.; Regulador de crescimento; Fotossíntese